(untitled) (Research, Society and Development, 2020)
The paper production chain connects several other productive links, such as recycling, which allows for a transition to a circular economy. Therefore, the importance of solid waste management, shared responsibility and selective collection is emphasized. In this context, the study aimed to analyze the role of associations and cooperatives in the metropolitan region of Belém do Pará, in the management of waste paper, in order to identify its work process and its economic, social and environmental importance. The study area comprised the metropolitan region of Belém-PA, and the research methodology is exploratory of the case study based on qualitative and quantitative data from the on-site analysis and interviews. Seventeen cooperatives were identified and six selected for the interviews. The results showed that the cooperative members perform household collection. The classification of the collected papers is carried out on white, mixed and cardboard scraps, in addition it was identified that the quantities are not regularly recorded and the sales prices of the material to large companies are lower than the national average. The cooperatives that receive government incentives, receive waste from fixed locations “door-to-door” and use rudimentary tools, characterizing vulnerable working conditions. The relevance of support from the public authorities and the private sector is highlighted to enable better working conditions and efficiency of the selective collection system. Thus, with the study, it was noticed interconnected social, economic and environmental issues, and that necessary improvements for good management must encompass public policies such as the inclusion of effective environmental education.